إدارة تعليم اللغة العربية للأغراض الخاصة في كلية علوم الصحة والطب بجامعة علاءالدين الإسلامية الحكومية بمكاسر سلاويسي الجنوبية - MUSGAMY, AWALIAH (ADARA, 2016)
Abstract: Teaching Arabic in a faculty that has a differently developing knowledge paradigm from Arabic like health field brings about many challenges. The challenges come to the low students’ prior knowledge and their motivation to learn Arabic. To overcome the challenges, teaching Arabic management must be able to accommodate the students’ knowledge background namely health field by implementing teaching Arabic for specific purpose.Keywords: Teaching Arabic Management, Teaching Arabic for Specific Purpose